2018
DOI: 10.1007/s10895-018-2226-3
|View full text |Cite
|
Sign up to set email alerts
|

Red Emitting Monoazo Disperse Dyes with Phenyl(1H-benzoimidazol-5-yl) Methanone as Inbuilt Photostabilizing Unit: Synthesis, Spectroscopic, Dyeing and DFT Studies

Abstract: Synthesis of three novel phenyl(1H-benzoimidazol-5-yl)methanone based fluorescent monoazo disperse dyes and their characterization by spectroscopic methods (H NMR, C NMR, IR and MS) are presented. Insertion of phenyl(1H-benzoimidazol-5-yl)methanone moiety bring about induced fluorescence properties and enhanced photostability as compared to the previously reported analogues (CI Solvent Yellow 14, 4-diethylamino-2-hydroxy-1-diazobenzene and 7-(diethylamino)-4-hydroxy-3-(phenyldiazenyl)-2H-chromen-2-one). Synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Compounds with high ε values can be used in potential applications even in low gloss conditions and show sublimation fastness. 33 In this study, the dye 3b showed higher ε values than the other dyes in both DMSO and DMF (Table 2). This could have resulted from the resonance stability of the nitro group bonded to the phenyl ring in the dye 3b.…”
Section: Solvent Effectsmentioning
confidence: 51%
“…Compounds with high ε values can be used in potential applications even in low gloss conditions and show sublimation fastness. 33 In this study, the dye 3b showed higher ε values than the other dyes in both DMSO and DMF (Table 2). This could have resulted from the resonance stability of the nitro group bonded to the phenyl ring in the dye 3b.…”
Section: Solvent Effectsmentioning
confidence: 51%
“…The solvatochromic behavior of the dyes 1–4 and 5–8 was studied with the help of Lippert [ 46 , 63 ] and Bakhshiev [ 63 ] plots. Lippert’s theory assumes that general solvent effects are present in the solvent medium and the polarizability of the solute molecule is neglected.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the 3c compound had higher ε and f values than other compounds (Table 4B). The compounds with high ε values may have potential applications in low gloss conditions and show greater sublimation fastness with respect to the others 47,48 …”
Section: Resultsmentioning
confidence: 99%